Pelatihan Kader Posyandu Dalam Deteksi Dini Penyakit Tidak Menular (PTM) - Noyumala, Noyumala; Idris, Idris; Nursiah, Andi; Suardi, Vivi Adriana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and heart disease continue to increase annually, including among productive-age individuals at the village level. As the spearhead of primary health care, Posyandu (Integrated Health Post) cadres play a crucial role in early NCD detection, yet their skills and knowledge remain limited. This Community Service Program (PKM) activity aims to improve the capacity of Posyandu cadres through training on risk factor identification, blood pressure measurement techniques, simple blood sugar tests, and recording and reporting NCD cases. Implementation methods included education, demonstrations, hands-on practice, and evaluation. The results of the activity showed a significant increase in cadres' knowledge and skills, as evidenced by a 48% increase in pre-test scores to 88% in the post-test. Cadres were also able to correctly measure blood pressure and blood sugar after the training. With this training, Posyandu cadres are expected to be able to conduct early NCD detection independently, regularly, and sustainably within Posyandu activities.